The correcting process of pronunciation at the beginners’ level in Кussian as foreign (Eurasian Journal of Philology Science and Education, 2018)
This article discusses the problem of learning pronunciation and phonetics of Russian as foreignlanguage. The purpose of the article is to review the characteristics of this type of competence, its importance to master the system of language. There have been characteristic features of acoustic and perceptual phonetics of foreigners as having a great influence on the process of mastering the speech activityin Russian. We generalize practical experience with the foreign audience at the initial stage of learningRussian as foreign language. Particular attention is drawn to the difficulties of perception and masteringthe Russian phonetic system of representatives of the peoples of Southeast Asia. Also there are analyzedsome characteristics of Russian phonemes as an example of the reduction vowels, consonants in stunning combinations of words with prepositions. And it is revealed the necessity of permanent system performance by foreigners of different exercises aimed at mastering the phonetics of the Russian language.These exercises should involve practicing the pronunciation, intonation, as well as work with varyingemphasis. The authors note that these skills must be received by students at the basic level of education.Phonetics language, its rules must be studied and practiced by students constantly